Pengaruh Penerapan Green Accounting terhadap Profitabilitas Pada Perusahaan Sektor Pertambangan - Reinamah, Clara Margilina; Faley, Hisner Glori; Sihombing, Liston (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This study aims to analyze the effect of green accounting on the profitability of mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. Green accounting in this study is proxied through the Corporate Performance Rating Program in Environmental Management (PROPER) rating. Data were analyzed using simple linear regression on 60 observation samples from 12 mining companies. The results of the study indicate that the implementation of green accounting as measured by the PROPER rating does not have a significant effect on the profitability of mining companies. This indicates that the company's environmental performance, as assessed by PROPER, has not been a determining factor in increasing the profitability of mining companies in Indonesia during the study period. This study implies that even though companies have made efforts to manage the environment in accordance with regulations, this is not necessarily positively correlated with increasing company profits.